The Prevalence and Risk Factors of Iron Deficiency Anemia Among Pregnant Women in Malaysia: A Systematic Review - Abd Rahman, Raudah; Idris, Idayu Badilla; Isa, Zaleha Md; Rahman, Rahana Abdul; Mahdy, Zaleha Abdullah (Frontiers in Nutrition, 2022)
Anemia in pregnancy is defined as a hemoglobin level of less than 11g/dl, and is commonly due to iron deficiency. This systematic review was conducted to determine the prevalence and risk factors of anemia and iron deficiency among pregnant women in Malaysia. A systematic literature search was conducted in Google Scholar, PubMed and Cochrane Library databases. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline. Eight studies comprising a total number of 2638 pregnant women were included in this review. Only two studies focused on iron deficiency, whereas the other six investigated anemia in pregnancy without specifying iron deficiency or any other nutritional cause for the anemia, signifying the lack of published literature on this important public health nutritional issue in Malaysia. The overall prevalence of anemia in pregnancy ranged from 19.3% to 57.4%, while the prevalence of iron deficiency was 31.6% to 34.6%. Factors that were significantly associated with anemia in pregnancy were extremes of reproductive age, late antenatal booking, non-compliance to hematinics, Indian ethnicity, being in the second or third trimester, low maternal educational level, low family income, and unemployment. The prevalence of anemia in pregnancy was found to be higher in rural compared to urban areas. Meanwhile, in terms of iron deficiency anemia, grandmultiparity, late antenatal booking and Indian ethnicity were significant determinants. It is certainly plausible that the anemia in pregnancy reported in these studies is not entirely secondary to iron deficiency and may be attributable to other nutritional deficiencies, emphasizing the importance of researching deeper into this subject. Nevertheless, in the meantime, focusing on iron supplementation in high-risk mothers with emphasis on compliance, seems to be the best option, in view of the high prevalence of iron deficiency found in this review.